Daytime Ionospheric TEC Weather Study Over Latin America. Issue 12 (22nd December 2018) - Romero‐Hernandez, E.; Denardini, C. M.; Takahashi, H.; Gonzalez‐Esparza, J. A.; Nogueira, P. A. B.; de Pádua, M. B.; Lotte, R. G.; Negreti, P. M. S.; Jonah, O. F.; Resende, L. C. A.; Rodriguez‐Martinez, M.; Sergeeva, M. A.; et al.
Abstract: The present work is the first of a two‐part weather study of the ionospheric Total Electron Content (TEC), based on data collected by four ground‐based Global Navigation Satellite System networks that cover the whole Latin America from the Patagonia to the north of Mexico. From the best of our knowledge, the maps presented here are the first TEC maps obtained using ground‐based data that covers the entire Latin America region, which represent an advance to the space weather monitoring and forecasting of the ionosphere. This work provides a qualitative and quantitative daytime analysis of the ionospheric TEC variation, which encompasses: (a) the response of TEC to the solar flux at midday; (b) the seasonal variation of TEC in different latitudinal ranges; and (c) the North‐South asymmetry of TEC over Latin America. The response to the solar flux is based on day‐to‐day TEC variations during two periods of different solar activity conditions: 2011 (ascending phase) and 2014 (maximum). The approximations of meridional wind component derived from Horizontal Wind Model‐14 model and h m F 2 obtained from International Reference Ionosphere model were used. Equinoctial asymmetries with an opposite configuration in high and moderate solar activity were identified in the TEC variation. For 2011, it was related to the solar flux change. However, in 2014, according to the h m F 2 variation, the influence of neutral wind becomes dominant. Among the results, we highlight an absence of winter anomaly in the Northern Hemisphere in 2014 and a stronger annual anomaly for latitudes under −20 ∘ . Key Points: The response of TEC to solar flux over Latin America is investigated The seasonal variation of TEC over Latin America during daytime is analyzed North‐South asymmetries of TEC over Latin America during daytime are identified